WAKTU KONTAK DAN PH OPTIMUM SISA BUANGAN BATU BATA TERAKTIVASI DI-(2-ETHYLHEXCYL) PHOSPHATE ACID (D2EHPA,) SEBAGAI PENJERAP PB 2+ - Fransina, Eirene Grace; Latupeirissa, Jolantje; Stefanus, Quendeline (Molluca Journal of Chemistry Education (MJoCE), 2018)
Determination of optimum pH and contact time, of broken brick from Latuhalat village as adsorbent of Pb2+ through impregnation with di-(2-ethylhexcyl) phosphate acid (D2EHPA) has been done. Bricks impregnated with di-(2-ethylhexcyl) phosphate acid concentration of 700 ppm to enlarge the surface area of ??adsorption on bricks. The result of analysis using AAS show that optimum contact time is 3 hours, optimum pH is 8, with weight of adsorbent is 0,2 g, adsorbate concentration is 100 ppm and adsorption capacity is 49,9985 mg/g adsorbent.